Youth and reproduction: demograhic, behavioral and reproductive profiles in the PNDS-2006 - Berquó, Elza; Garcia, Sandra; Lima, Liliam (Revista de Saúde Pública, 2012)
OBJECTIVE: Analyze the sociodemographic characteristics and the sexual and reproductive behavior of young women. METHODS: A cross-sectional nationally representative study was performed about sexual, contraceptive and reproductive behavior with 2,991 women age 15 to 20 years in the National Survey on Demography and Health of Women and Children, 2006. The women were classified into three groups: sexual initiation and pregnancy before the age of 20 (group A); sexual initiation but no pregnancy before the age of 20 (group B) and no sexual initiation (group C). Women until age 25 years were included in the study about reasons for becoming pregnant and the implications for their lives. Statistical analysis considered survey weights and the complex sample design. The association between two categorical variables was assessed by chi-square test. The behavior variables were assessed using a global linear model. RESULTS: Women in group A were mainly black, poorer and with lower education level. These women had an early sexual initiation, less safe contraceptive behavior and less knowledge of reproduction physiology in comparison with group B; young women in group C were characterized by greater attendance at school and 1/3 of this group claimed to maintain their virginity until marriage. For women up to the age of 25, pregnancy before 20 years was perceived as having more positive than negative impacts upon their love life, spousal relationships, social lives and self-esteem. CONCLUSIONS: There is a significant association between pregnancy before the age of 20 and higher poverty and lower educational level. In the absence of better living conditions and opportunities, pregnancy, although unplanned, becomes "a plan for life", and is not seen as a lack of life planning.